Boletim Atlas ODS Amazonas V.2 N.6 - Especial COVID-19 - Pereira, Henrique dos Santos (Brasil, 2020)
The Special Edition of SDG Amazonas Atlas Report was created to present reflections and projections, in addition to maps and illustrations, of the coronavirus pandemic of the State of Amazonas. In this report we present two studies about mobility and the COVID-19 pandemic in Amazonas. Exploring indicators of intensity of urban traffic in Manaus and of flow between cities, the researchers present their analysis about the relationship between mobility and mortality and the spread of the disease.